The Practitioner’s Identity and Participation in Strategy Workshops. An Ethnographic Study - Sund, Christine; Le Loarne Lemaire, Séverine (Management international / International Management / Gestiòn Internacional, 2022)
Participation, a key component of strategy work, is examined to focus on bottom-up strategy work in this longitudinal study based on ob¬servations of a global firm’s strategy workshop. Results show some middle managers are better positioned than others to engage in strategy work because of previous international experience, prior strategy-workshop insights, and cultural, behavioral, and personality traits. A typology of strategist profiles identify those who characteristically participate, and associated vignettes reveal participation approaches. The research concludes strategy-workshop proposal consideration and adoption are subject to the participant’s identity, adding to the debate on the role identity plays in strategizing practices.